Character Education Based on Tidung Local Wisdom: A Study on the Tidung Ethnicity of North Kalimantan - Bukhari, Akhmad; Arbain, Muhammad; Gusniati, Yeisi (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study highlights various national issues, especially the increasing concern for moral degradation within society, affecting both ordinary citizens and the educated alike. This degradation manifests in prevalent acts such as student brawls, drug abuse, promiscuity, immoral acts, and even other unlawful behaviors like widespread corruption. Addressing these issues requires an approach rooted in local wisdom, one notable example being the local wisdom values of the Tidung tribe in North Kalimantan, which can serve as a foundation for developing character education in Indonesia. This research aims to explore the Tidung tribe's local wisdom values that can subsequently be implemented in developing character education based on Tidung local wisdom. The study employs a qualitative descriptive approach, utilizing primary data obtained through observation, interviews, and documentation involving customary figures, education stakeholders, teachers, and Tidung tribal community members. Data analysis involves data reduction, display, verification, and triangulation. The findings of this study indicate: ngejaga tengkayu (protecting the marine ecosystems), tenguyun (like to cooperate), suang bagas begambus kamad bagas inteladus (simplicity and independence), tulid dalom ukum (honesty), beadob de ulun tuo (manners to parents), bais penyawo (kind), impong de lunas insuway (having a high sense of solidarity), tetulu (life advice), and bepakot (deliberation). These local wisdom values of the Tidung tribe can form the basis for strengthening character education in Indonesia, especially in North Kalimantan.